1994
DOI: 10.1055/s-2007-1021028
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Effect of Bicycle Exercise on Blood Mononuclear Cell Proliferative Responses and Subsets is Mediated by Epinephrine

Abstract: The present study was designed to test the hypothesis that the exercise-induced changes in blood mononuclear cell (BMNC) subsets, BMNC proliferative responses and lymphokine activated killer (LAK) cell activity are mediated by increased epinephrine concentrations. Healthy male volunteers 1) exercised on a bicycle ergometer (75% of VO2max, 1 h) and 2) on another day were given epinephrine as an intravenous infusion to obtain plasma epinephrine concentrations comparable with those seen during exercise. Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 21 publications
(22 reference statements)
6
54
1
5
Order By: Relevance
“…18,19 Previous studies showed that prostaglandins from activated monocytes and neutrophils that have migrated into damaged tissue might contribute to the reduction of NKCA. 9,11 In the present study, prostaglandins significantly increased after exercise in SCI subjects but not in able-bodied persons. Since the intensity of exercise in SCI subjects was similar to that of able-bodied subjects, we suggest that arm cranking during ergometer exercise in SCI subjects could result in compression of the tissue in paralyzed trunk, hip and lower limbs and induce distress and/or microdamage in the paralyzed area.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…18,19 Previous studies showed that prostaglandins from activated monocytes and neutrophils that have migrated into damaged tissue might contribute to the reduction of NKCA. 9,11 In the present study, prostaglandins significantly increased after exercise in SCI subjects but not in able-bodied persons. Since the intensity of exercise in SCI subjects was similar to that of able-bodied subjects, we suggest that arm cranking during ergometer exercise in SCI subjects could result in compression of the tissue in paralyzed trunk, hip and lower limbs and induce distress and/or microdamage in the paralyzed area.…”
Section: Discussioncontrasting
confidence: 41%
“…12,13 NKCA is stimulated by adrenaline, 3 suppressed by cortisol 10 and inhibited by prostaglandins. 9,11 The purpose of this study was to investigate the pattern of NKCA during exercise in SCI persons and to determine the mechanism(s) of any exerciseinduced change in NKCA, including the effects of adrenaline, PGE 2 and cortisol. For this purpose, we examined NKCA response to 2-h arm ergometer exercise at 60% of maximum oxygen consumption (VO 2max ) in SCI and ablebodied persons.…”
Section: Introductionmentioning
confidence: 99%
“…We show that stresslike increases in epinephrine concentrations invoke a specific increase in immune subpopulations with cytotoxic effector potential, namely, effector CD8 + T cells It has been repeatedly demonstrated that the number of immune cells increases after physical exercise or mental stress, with the most pronounced increases occurring in NK cell and CD8 + cytotoxic T cell counts (3,5,16,34), whereas both populations are decreased when endogenous catecholamines are suppressed by stellate ganglion block (40). These effects are caused by adrenal medullary epinephrine binding to b2-adrenoceptors on PBMCs, with high and intermediate levels of b2-adrenoceptor expression on NK cells and cytotoxic T cells, respectively (1,3,7,8,19,33,41). Our findings substantially expand these previous findings in showing that the epinephrine-induced increase in circulating immune cells is highly specific to cytotoxic effector subtypes, namely, effector CD8 + T cells, g/d T cells, NKT-like cells, cytotoxic NK cells, and proinflammatory monocytes, whereas no change is seen for cells lacking any cytotoxic potential, namely, CD4 + T cells, CD8 + T cells at their early stage of differentiation, immunomodulatory NK cells, and conventional monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…epinephrine infusion at concentrations within the physiological normal range on 14 different T cell, NK cell, and monocyte subsets. Epinephrine was chosen because it is well-known, via binding with high affinity to the b2-adrenoceptor of PBMCs, to play a key role in mediating acute stress-induced leukocytosis (1)(2)(3)(32)(33)(34) + proinflammatory monocytes. Analysis of adhesion molecule and chemokine receptor expression reveals a specific profile in these cells, characterized by high expression of CD11a and CX3CR1 (fractalkine receptor).…”
mentioning
confidence: 99%
“…25 Second, injection of epinephrine induced monocytosis similar to exercise. 26 Last, one study has demonstrated that administration of propranolol can abrogate the exerciseinduced rise in blood monocytes. 27 This finding needs to be repeated.…”
Section: Monocyte/macrophage Numbermentioning
confidence: 99%